Penerapan Model Kooperatif Tipe Numbered Heads Together (NHT) untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika Kelas V MI Ar-Raudhah - Anwar, Eva Naulia; Syabrina, Muhammad; Sulistyowati, Sulistyowati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
The objectives of this study are to: (1) Describe the implementation of mathematics learning using a cooperative model of the numbered heads together (NHT) type in class V MI Ar-Raudhah. (2) Improving mathematics learning outcomes with the numbered heads together (NHT) cooperative model in class V MI Ar-Raudhah. The method used in this study is classroom action research (PTK) which is carried out in cycles with the Kurt Lewin model which consists of planning, implementation, observation and reflection. The research subjects consisted of 23 students. The data collection techniques in this research uses observation to see the activities of teachers and students, interviews with Mrs. Nazila as a mathematics teacher, documentation during the research proses in class V and formative tests in the form of intial and final tests. The data obtained was analyzed by quantitative descriptive analysis, namely the processing of average and percentage numbers. The result of this research show that (1) the implementation of the numbered heads together (NHT) type cooperative model in the first cycle as a result of the analysis of students in the first cycle obtained a percentage of 79.37% with good criteria and increased in the second cycle to 87.5% with very good criteria. (2) the use of the numbered heads together (NHT) type cooperative model can improve mathematics learning outcomes in class V MI Ar-Raudhah, as seen from the classical completeness result in the first cycle reaching 65% and increasing in the second cycle to 78%. And obtained N Gain in cycle I of 0.15 and cycle II of 0.63. As well obtaining N Gain in the first cycle of 0.15 with the “Low” category and the second cycle of 0.63 with the “Medium” category. Based on the results of the research obtained by the researchers, it can be concluded that using a cooperative model of the numbered heads together (NHT) type can improve students’ mathematics learning outcomes. The increase can also be seen with an increased N Gain.